[OP.1A.11] RESPONSES OF INSULIN AND BLOOD PRESSURE TO DIETARY SODIUM INTERVENTION IN CHINESE POPULATION: THE GENSALT STUDY. (September 2017) - Chen, S.; Liu, F.; Yang, X.; Huang, J.; Lu, X.; Chen, J.; Cao, J.; Li, J.; Li, H.; Wang, L.; Liu, D.; Gu, D.
Abstract : Objective: Insulin resistance (IR) is the crucial mechanism for metabolic syndrome, and a risk factor of cardiovascular disease (CVD). Salt restriction is recommended to decrease the risk of CVD. Nevertheless, recent studies have suggested that low sodium intake increases IR. We aimed to examine the association between IR and salt sensitivity of blood pressure (BP) in the GenSalt study. Design and method: We conducted a 7-day low-sodium intervention (51.3 mmol of sodium per day) followed by a 7-day high-sodium intervention (307.8 mmol of sodium per day) in population from the northern rural China. BP measurements were obtained at baseline and each dietary intervention using a random-zero sphygmomanometer. The serum insulin levels were analyzed using an automated two-site radioimmunoassay (Cisbio Bioassays, France). The index of IR was estimated as HOMA-IR = (fasting glucose (mg/dL) X fasting insulin (μU/mL))/405. Correlations between IR and BP were derived adjusting for age and gender. The associations between insulin response to sodium intervention and BP response to sodium intervention were tested using linear mixed-effect regression model. Results: A total of 1822 participants were included in the final analysis. Fasting serum glucose, insulin and HOMA-IR were higher during low-sodium intervention and lower during high-sodium intervention. The mean glucose, insulin and HOMA-IR were 86.4 mg/dl, 6.1 uIU/ml and 1.3 at baseline, 89.9 mg/dl, 6.4 uIU/ml and 1.4 at the end of low-sodium intervention, 85.3 mg/dl, 5.4 uIU/ml and 1.2 at the end of high-sodium intervention. After adjustment for age and gender, insulin was correlated with BP (SBP: r = 0.15, P < 0.0001; DBP: r = 0.09, P < 0.0001; MAP: r = 0.13, P < 0.0001) at baseline; change in insulin was correlated with BP response (SBP: r = −0.04, P = 0.11; DBP: r = 0.05, P = 0.04; MAP: r = −0.05, P = 0.04) to low-sodium intervention. In linear mixed-effect regression model, the increase in insulin was associated with decrease in SBP (β = −0.07, p = 0.002), DBP (β = −0.06, p = 0.03) and MAP (β = −0.09, p = 0.003) during low-sodium intervention. Conclusions: We concluded that change in inzsulin was significantly associated with BP change during low-sodium intervention. The specific mechanism is not fully understood and further functional studies are warranted to clarify their relationship.